Best practice in leading research and evaluation for interprofessional education and collaborative practice - Forman, Dawn; Thistlethwaite, J. (2016)
© The Author(s) 2016.The decade since the mid-2000s has reignited an interest in interprofessional education (IPE) and collaborative practice (CP) globally. The editors of this book believe this was due at least in part to the publication of the World Health Organization (2010) Framework for Action on Interprofessional Education and Collaborative Practice, which not only reviewed examples of interprofessional education internationally but also provided a framework that linked interprofessional education (IPE) to collaborative practice (CP) and improved health care provision. Our two books (Forman, Jones, & Thistlethwaite, 2014, 2015) took into account further work by the World Health Organization (WHO) (2013) and policies which were being implemented in diverse countries, such as by Health Education England (2014). We also included reports on research studies such as Interprofessional Curriculum Renewal and Australia (2014) in Australia, to provide global examples of how IPE and CP were being taken forward in higher education institutions and communities.